Effectiveness of Local Wisdom-Based LKPD on GCF and LCM to Improve Fifth-Grade Students’ Mathematical Critical Thinking in Makmur District - Juniati, Juniati; Maisura, Maisura; Mukhlesiyeni , Ety (Journal of Educational Sciences, 2026)
This study aims to determine the improvement of fifth-grade students’ mathematical critical thinking skills after using local wisdom-based student worksheets (LKPD) on the topics of Greatest Common Factor (GCF) and Least Common Multiple (LCM), to compare the results between the experimental and control classes, and to assess the effectiveness of the LKPD. The research employed a quasi-experimental method with a non-randomized control group pretest-posttest design. The study was conducted at SD Negeri 2 Makmur (experimental class) and SD Negeri 8 Makmur (control class) during the 2025/2026 academic year, using a simple random sampling technique. The instrument used was a valid and reliable essay test (α = 0.765). Data were analyzed using normality, homogeneity, t-test, and two-way ANOVA with the assistance of SPSS 27. The results showed a significant improvement in mathematical critical thinking skills in the class that used local wisdom-based LKPD compared to the conventional method. The LKPD proved to be effective as it connects mathematics learning with local cultural contexts, making it more meaningful and engaging for students.